A elaboração de um repertório semibilíngue de somatismos fraseológicos do português brasileiro para aprendizes argentinos - Rocha, Camila Maria Corrêa [UNESP] (2014)
Brazilian Portuguese (BP) is a linguistic variant that is getting increasingly included as a foreign language (FL) in school contexts in Latin American countries, especially in Argentina. In that country, the law nº 26.468/2009 was sanctioned in 2009 granting the teaching of Portuguese as a FL to high school students. However, despite this growing interest in our linguistic variant, the Argentinian government has not provided enough support for the necessary expansion of Portuguese in their country. It is observable that a limited approach to the teaching of this language has been applied, with few resources to special lexis, including idiomatic expressions (IEs), a lexical content of extreme relevance for Spanish speakers. The IEs are complex lexis whose meaning is not simply derived from the meaning of each word out of which it is made (ORTIZ ÁLVAREZ, 2000). Thus, in the context of teaching Portuguese as a foreign language (PFL) as well as in the teaching and learning of any other FL, referrals to the difficulties related to learning IEs are common for them being culturally embedded by lexical units. The study of IEs using the monolingual lexicographical perspective derives from the belief that general monolingual dictionaries could be a means through which learners of PFL would have access to IEs in order to understand them in all their aspects, it does not matter whether they are semantic or cultural ones. The main objective of this study is to create a somatic semibilingual repertoire (SSR) with pedagogical purpose of the Portuguese language with its equivalent in the Argentinian variant of Spanish based on the tenets of Phraseology, Lexicography, Pedagogical Lexicography and Lexiculture. The accomplishment of such an objective will require the execution of three specific objectives prior to it: a) verify in the web, the biggest data base available today in the world (RIVA, 2008), the number of occurrences of 76 IEs belonging to ...